2014
DOI: 10.1063/1.4862648
|View full text |Cite
|
Sign up to set email alerts
|

Water confinement in nanoporous silica materials

Abstract: The influence of the surface polarity of cylindrical silica nanopores and the presence of Na(+) ions as compensating charges on the structure and dynamics of confined water has been investigated by molecular dynamics simulations. A comparison between three different matrixes has been included: a protonated nanopore (PP, with SiOH groups), a deprotonated material (DP, with negatively charged surface groups), and a compensated-charge framework (CC, with sodium cations compensating the negative surface charge). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 40 publications
3
48
0
Order By: Relevance
“…Indeed, it offers unique opportunities to connect some macroscopic properties to a microscopic description of the physical phenomena involved in the separation. Although MD has been already applied to investigate both water and ion transports through nanopores with well-defined geometries [12][13][14][15][16][17][18], the limited information about the three-dimensional molecular structure of RO polyamide membranes makes the use of this computational method much more challenging. As a result, the identification and the understanding at a microscopic level of the underlying mechanisms governing water and ion transport through RO membranes are proceeding very slowly and only few studies reported on the attempt of building full atomistic models of RO polyamide membranes [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it offers unique opportunities to connect some macroscopic properties to a microscopic description of the physical phenomena involved in the separation. Although MD has been already applied to investigate both water and ion transports through nanopores with well-defined geometries [12][13][14][15][16][17][18], the limited information about the three-dimensional molecular structure of RO polyamide membranes makes the use of this computational method much more challenging. As a result, the identification and the understanding at a microscopic level of the underlying mechanisms governing water and ion transport through RO membranes are proceeding very slowly and only few studies reported on the attempt of building full atomistic models of RO polyamide membranes [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…35 g OH (r)r 2 dr . (9) g OH (r) in Eq. 9 is calculated for oxygen atoms in each layer with a width of 1.0 A.…”
Section: Hydrogen-bond Configurations and Dynamicsmentioning
confidence: 99%
“…The behavior of confined water has been widely studied by both theoretical [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and experimental [26][27][28][29][30][31] techniques in the past few decades. These works have indicated that the properties of confined water may strongly differ from that of bulk water depending on surface properties and size of confinement space.…”
Section: Introductionmentioning
confidence: 99%
“…However, just a few publications give some results on orientational behaviour of confined water [17,21,22].…”
Section: Introductionmentioning
confidence: 98%
“…However, in this case, mostly silica pores were considered (see e.g. [15][16][17]), although some other confining substances were investigated too (e.g. in [18], water confined in porous AlPO 4 was studied).…”
Section: Introductionmentioning
confidence: 99%